STIMULASI PERKEMBANGAN KEAKSARAAN ANAK USIA 4–5 TAHUN MENGGUNAKAN BAHAN SISA DI TK SOSIAL WAGOLA - Ode, Inang Wa; Jeti, La; Henny, Henny (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe how the stimulation of literacy development in children aged 4–5 years can be carried out using leftover materials as learning media at TK Sosial Wagola. The research employed a descriptive qualitative approach with the Participatory Action Research (PAR) method. Data collection techniques included observation, interviews, and documentation, which were analyzed using the Miles and Huberman model consisting of three stages: data reduction, data display, and conclusion drawing. The findings indicate that utilizing leftover materials such as used paper, cardboard, snack packaging, and skewers is effective in stimulating children's literacy skills. The children demonstrated progress in recognizing letters, identifying object names based on initial sounds, writing their own names, and distinguishing between vowels and consonants. The use of leftover materials also made the learning process more enjoyable, contextual, and stimulated children's creativity. This study reveals that environmentally-based alternative media can enhance early childhood literacy naturally through meaningful play-based learning.